Female Genital Tuberculosis: Clinical Presentation, Current Diagnosis, and Treatment - Dian Tjahyadi; Bejo Ropii; Kevin Dominique Tjandraprawira; Ida Parwati; Tono Djuwantono; Wiryawan Permadi; Tinchiu Li (Hindawi Limited, 2022)
Female genital tuberculosis is a disease caused by Mycobacterium tuberculosis infection in the female reproductive tract. The disease burden among women leads to infertility is significant, especially in developing countries. The bacteria can spread from the lung into the reproductive organ through lymphatic or hematogenous. Many patients present with atypical symptoms, which mimic other gynecological conditions. Several investigations are needed to establish the diagnosis. Almost all cases of genital TB affect the fallopian tube and cause infertility in patients and endometrial involvement. Current treatment still relies on antituberculosis therapy with a combination of tubal surgery. The present review describes the epidemiological data, clinical presentation, diagnosis, and currently available treatment to cure the disease and for in vitro fertilization.